Molecular cytogenetic analysis of heterochromatin in the chromosomes of tilapia, Oreochromis niloticus (Teleostei : Cichlidae) - Oliveira, C.; Wright, J. M. (Kluwer Academic Publ, 1998)
The structure of the heterochromatic bands in mitotic chromosomes of the important tropical aquaculture species of tilapia, Oreochromis niloticus, was investigated by the combination of the C-banding technique, chromosomal digestion with two restriction endonucleases and fluorescence in situ hybridization (FISH) of two satellite DNAs (SATA and SATB). The tilapia chromosomes presented heterochromatic bands in the centromeres and in the short arms of almost all chromosomes that were differentially digested by the restriction endonucleases HaeIII and EcoRI. FISH of SATA showed that the satellite sequence is distributed in the centromeric region of all chromosomes of tilapia. FISH also revealed an intense hybridization signal for SATB in only one chromosome pair, but less intense signals were also present in several other pairs. The digestion of tilapia chromosomes by HaeIII and EcoRI was positively correlated with the position of SATA and SATB in chromosomes as revealed by FISH. The results obtained may be useful in future molecular and genetic studies of tilapias.
Keywords: chromosome structure; fish cytogenetics; fluorescence in situ hybridization; heterochromatin; satellite DNA